Pengaruh Partisipasi Anggaran Terhadap Kinerja Manajerial dengan Komitmen Organisasi dan Motivasi Sebagai Variabel Intervening - Guillerma Giusti; Alwan Sri Kustono; Rochman Effendi (UPT Penerbitan Universitas Jember, 2018)
This study aims to show the causal relationship of participation with commitment and motivation for mangerial performance. Partial Least Square (PLS) is used with purposive sampling to explain causal relationships and linkages between several variables. The research is sourced from the permanent employees of Micro, Small and Medium Entreprise Service Office of Jember Regency as many as 45 permanent employees. The results of this study indicate that budget participation has a positive effect on managerial performance, organizational commitment and motivation. Furthermore, organizational commitment and motivation have a positive effect on managerial performance, and the result of final test of motivation have positive effect to organizational commitment.Keywords: Managerial Performance, Organizational Commitment, Motivation, Budget Participation Abstract